5-2x+4=4-6-3x

Simple and best practice solution for 5-2x+4=4-6-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-2x+4=4-6-3x equation:



5-2x+4=4-6-3x
We move all terms to the left:
5-2x+4-(4-6-3x)=0
We add all the numbers together, and all the variables
-2x-(-3x-2)+5+4=0
We add all the numbers together, and all the variables
-2x-(-3x-2)+9=0
We get rid of parentheses
-2x+3x+2+9=0
We add all the numbers together, and all the variables
x+11=0
We move all terms containing x to the left, all other terms to the right
x=-11

See similar equations:

| 0.5x/3000000=0.5-2250000/2000000 | | 3u2=12u-3 | | 21x-7=21+14x | | 20x/5=40 | | 9a+6=8-3a | | x-(x*0.15)=5+8.95 | | -8=z/2 | | -10=3x+x | | 10x+4=-13 | | (2^3x-1)=1/32 | | 2^3x-1=1/32 | | 17=2(3x+1)x | | 4x-8+5=5x+10 | | 8(x+2)-3(x-3)=2(x-3)+2(x-2) | | x2+6=3 | | 18-3x+2=2x+5 | | 2*3+x=7 | | x+2*3=7 | | x=2*3=7 | | 2q-16=4-3q | | 3+2(x+5)=13+2x | | 9/2(x+3)=28 | | Z=-4+4i | | (x+1995)(x+1997)(x+1999)(x+2001)+16=0 | | 3k/2+k/5=8 | | (x^2)^2=16 | | F(x)=3^2x+6 | | 7+20+x=180 | | 4x^2-4.5x+1.125=0 | | |w|+5=9 | | 1p+2=p+2 | | 12=x+6-x |

Equations solver categories